2022
DOI: 10.3390/ma15082714
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Parameters on the Performance of Alkali-Activated Slag/Fly Ash Composite System

Abstract: In order to study the influence law of each parameter on the performance of the alkali-activated composite gelling system, the influence degree was sorted, and the most important parameter affecting each performance was found. The solution of liquid water glass and solid sodium hydroxide was used as the alkaline activator, and the mixing ratio was designed by the orthogonal test method. The effects of four parameters of fly ash content, water glass modulus, water glass solid content, and water–solid ratio on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The flow test values for the produced composites indicate that the addition of both water and zinc oxide increases the fluidity of the mixtures, which was also confirmed by the research of Zhang et al [ 23 ], who studied the effect of various parameters on alkali-activated slag/fly ash composites. They observed that fluidity increased with increasing fly ash content in the mixture.…”
Section: Discussionsupporting
confidence: 73%
“…The flow test values for the produced composites indicate that the addition of both water and zinc oxide increases the fluidity of the mixtures, which was also confirmed by the research of Zhang et al [ 23 ], who studied the effect of various parameters on alkali-activated slag/fly ash composites. They observed that fluidity increased with increasing fly ash content in the mixture.…”
Section: Discussionsupporting
confidence: 73%
“…The main reasons for the inhibition of AASRSS hydration by NaSt are as follows: (1) NaSt adsorbs on the surface of silica-aluminate precursor particles, which prevents the precursor and alkali activator from reacting in contact with each other [24]. (2) The wrapping effect of NaSt on the solution in the slurry reduces the liquid-phase distribution of the system to some extent, resulting in a reduction in the contact area between the precursor particles and the alkali activator [26]. To further explore the mechanisms behind these findings of compressive strength and water sorptivity, the reaction process, reaction products and pore structure were carefully examined, and the results are presented in the following sections.…”
Section: Isothermal Calorimetrymentioning
confidence: 99%
“…The main reasons for the inhibition of AASRSS hydration by NaSt are as follows: (1) NaSt adsorbs on the surface of silica-aluminate precursor particles, which prevents the precursor and alkali activator from reacting in contact with each other [24]. (2) The wrapping effect of NaSt on the solution in the slurry reduces the liquid-phase distribution of the system to some extent, resulting in a reduction in the contact area between the precursor particles and the alkali activator [26].…”
Section: Isothermal Calorimetrymentioning
confidence: 99%
“…This is because when the dosage of sodium silicate is 50 g, the concentration of OH − in the system is low, the erosion of precursor is slow, and the slurry is mainly manifested as the highly viscous sodium silicate aqueous solution and suspended particle mixture. At this point, if the content of sodium silicate is slightly increased, the concentration of OH − is enough to erode the precursor, while if the content of sodium silicate continues to increase, excessive OH − will form Ca (OH) 2 with Ca 2+ , inhibiting an increase in the fluidity [38].…”
Section: Workabilitymentioning
confidence: 99%